The Relationship between Nutrient Intake and Work Motivation with Employee Performance at PT. Pancaran Samudera Shipyard - Ade Amalia Husna; Edi Sukamto; Riana Pangestu Utami (PT FORMOSA CENDEKIA GLOBAL, 2023)
Health is the main key to improving performance. Nutritional intake affects health and physical ability to carry out tasks. Motivation is the main driver of carrying out tasks with high enthusiasm. This research aims to analyze the relationship between nutritional intake and work motivation with the performance of employees at PT. Pancaran Samudera Shipyard. The method used was cross-sectional with 40 respondents using purposive sampling technique. Data was collected through 2 x 24 hour food recall interviews for nutritional intake, work motivation questionnaires, and performance assessments with KPI scores. The results show that there is a relationship between energy intake, carbohydrate intake, and work motivation with employee performance. However, there was no significant relationship between protein and fat intake and performance. So it can be concluded that energy intake, carbohydrates and work motivation are related to employee performance.